2020
DOI: 10.1039/d0sm01132k
|View full text |Cite
|
Sign up to set email alerts
|

A facile approach to obtain highly tough and stretchable LAPONITE®-based nanocomposite hydrogels

Abstract: Laponite sheets have been widely used for the preparation of tough nanocomposite hydrogels for enticing applications, however, their inferior dispersion in aqueous media resulting from the electrostatic interactions between the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…[12,13] LAP clusters in polymers markedly affect the homogeneity of nanocomposites, resulting in a decrease in mechanical properties, while exfoliated and intercalated LAP can be homodispersed into polymers, leading to a cross-linking effect and therefore enhancing the mechanical properties. [31,32] Therefore, aqueous exfoliation of LAP is more commonly used for polymer functionalization. To address this issue, chemical modification is usually applied to completely exfoliate hydrophilic LAP in hydrophobic polymers, but it can cause premature degradation of polymers or can decrease the polymers' mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…[12,13] LAP clusters in polymers markedly affect the homogeneity of nanocomposites, resulting in a decrease in mechanical properties, while exfoliated and intercalated LAP can be homodispersed into polymers, leading to a cross-linking effect and therefore enhancing the mechanical properties. [31,32] Therefore, aqueous exfoliation of LAP is more commonly used for polymer functionalization. To address this issue, chemical modification is usually applied to completely exfoliate hydrophilic LAP in hydrophobic polymers, but it can cause premature degradation of polymers or can decrease the polymers' mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Recently, an increasing number of studies have shown the efficacy of LAP-containing materials in the osteogenesis of BMSCs and osteoblasts as well as their ability to promote bone regeneration. [38][39][40] Furthermore, LAP has been shown to degrade into non-toxic components (Na + , Mg 2+ , Si(OH) 4 , Li + ) in physiological conditions, which can promote cellular adhesion and stimulate osteogenesis. 41 Herein, we show the successful development of an RSF/LAP 3D porous scaffold by simply mixing LAP dispersion in a RSF aqueous solution, followed by the previously established procedure (n-butanol addition coupled with freezing treatment).…”
Section: Introductionmentioning
confidence: 99%
“…LAP can act as a filler in hydrogels to promote mechanical properties and tune bone regeneration by regulating the stiffness of hydrogels [ 16–18 ]. Furthermore, its hydrophilic surface and negative charge can stimulate protein adsorption to increase cell adhesion and can be used as a therapeutic delivery vehicle to deliver a range of molecules [ 18 , 19 ]. An increasing number of studies have confirmed the bioactivity of LAP-containing biomaterials in the osteogenesis of BMSCs and osteoblasts and the promotion of bone regeneration in different bone defects [ 18 , 20–22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, its hydrophilic surface and negative charge can stimulate protein adsorption to increase cell adhesion and can be used as a therapeutic delivery vehicle to deliver a range of molecules [ 18 , 19 ]. An increasing number of studies have confirmed the bioactivity of LAP-containing biomaterials in the osteogenesis of BMSCs and osteoblasts and the promotion of bone regeneration in different bone defects [ 18 , 20–22 ]. Most of them focused on incorporation of LAP into different polymers (such as PCL and PLGA) to obtain functionalized fibrous membranes via electrospinning for potential bone regeneration applications [ 22–26 ].…”
Section: Introductionmentioning
confidence: 99%